2022
DOI: 10.3389/fpsyg.2022.1034203
|View full text |Cite
|
Sign up to set email alerts
|

Negative workplace gossip and turnover intention among Chinese rural preschool teachers: The mediation of ego depletion and the moderation of bianzhi

Abstract: IntroductionIn China, the high turnover rates of teachers have become one of the biggest obstacles to the development of rural preschool education. Objective: Based on the social information processing theory and the strength model of selfcontrol, this study examined the relationship between negative workplace gossip and turnover intention and the role of ego depletion and bianzhi in this relationship.MethodsThe questionnaire method was applied, and 411 rural preschool teachers in Hubei Province, China, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…It is pervasive and unavoidable in workplace settings. Negative workplace gossip has been found to have a range of negative impacts on the gossiped targets, such as increased engagement in political acts ( Cheng et al, 2020 ), emotional exhaustion ( Wu et al, 2018 ), reduced service performance ( Ye et al, 2019 ), and even the intention to resign ( He and Wei, 2022 ). In the context of China, a collectivist nation that places significant importance on relationships, interpersonal relationships carry more weight in Chinese society than in Western society.…”
Section: Introductionmentioning
confidence: 99%
“…It is pervasive and unavoidable in workplace settings. Negative workplace gossip has been found to have a range of negative impacts on the gossiped targets, such as increased engagement in political acts ( Cheng et al, 2020 ), emotional exhaustion ( Wu et al, 2018 ), reduced service performance ( Ye et al, 2019 ), and even the intention to resign ( He and Wei, 2022 ). In the context of China, a collectivist nation that places significant importance on relationships, interpersonal relationships carry more weight in Chinese society than in Western society.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by prior studies (e.g., Duffy et al, 2018), career calling can provide teachers with sufficient internal motivation to resist massive job burnout and intense turnover intentions and enhance their well-being and job performance. Given the intense job burnout and high turnover rates of kindergarten teachers (Guo et al, 2022; He & Wei, 2022), how to help kindergarten teachers perceive a strong career calling needs to be actively explored.…”
Section: Introductionmentioning
confidence: 99%
“…Turnover intention is the strongest indicator of actual turnover behavior [11], defined as the inclination to quit [12]. Prior research has demonstrated that a variety of individual and environmental factors affect rural kindergarten teachers' intention to leave their positions [13][14][15][16]. Leadership styles, which are significant environmental variables, have been shown to influence kindergarten teachers' intention to quit.…”
Section: Introductionmentioning
confidence: 99%